Analisis Peramalan Nilai Tukar Petani di Provinsi Jawa Barat - Jolanda, Hanifah Putri; Sulandjari, Kuswarini; Wijaya, I Putu Eka (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Farmer’s term of trade is a comparison between the price index paid by farmers and the price index paid by farmers, expressed as a percentage and used as an indicator to measure the level of farmer welfare. West Java has fluctuating Farmer’s term of trade of food crops, horticultural crops, and community plantations. This study aims to determine the best forecasting method and forecast Farmer’s term of trade of food crops, horticultural crops, and community plantations in West Java for the next 60 months. The research method used is descriptive analysis with a quantitative approach. This study uses secondary data in the form of time series from 2013-2021 totaling 108 periods sourced from the Statistics Indonesia and the Ministry of Agriculture. Data is processed using Minitab 20 application and Microsoft Excel. The data analysis techniques used are linear trend forecasting, quadratic trend, and exponential trend. Based on the smallest MAPE, MAD, and MSD values, the best method of forecasting Farmer’s term of trade of food crop and horticultural crops is a quadratic trend, while forecasting Farmer’s term of trade of smallholder plantation farmers is a linear trend. The forecasting of Farmer’s term of trade of food crop farmers has the equation model  = 101.25 + 0.0737X - 0.000964X2, horticultural crops have the equation model   = 105.28 + 0.1042X - 0.001561X2 , and smallholder plantation crops have the equation model   = 100.156 - 0.04342X. The results of forecasting Farmer’s term of trade of food crops, horticultural crops, and community plantations each have an average value of 92.6753%; 89.3132% and 94.14342%.